A Study on Muslim University Students in Indonesia: The Mediating Role of Resilience in the Effects of Religiousity, Social Support, Self-Efficacy on Subjective Well-being - Baidi Bukhori; Syamsul Ma'arif; Siti Aisyah binti Panatik; Ide Bagus Siaputra; Abdullah Azzam Al Afghani (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung in collaboration with Asosiasi Bimbingan dan Konseling Indonesia (ABKIN), 2022)
Subjective well-being is an essential part of mental health in both religious and non-religious communities. On a global scale, most research on the relationship between religiosity and subjective well-being is conducted on English-speaking, Western, and Christian populations. This large-scale study is expected to complement and balance previous research by reporting the important role of resilience as a mediator in the relationship between religiosity, social support, and self-efficacy on subjective well-being based on a sample of Indonesians, the world's largest Muslim population. Data collection uses adaptation of standardized scales, namely the Positive Affect Negative Affect Schedule (PANAS) and Satisfaction with Life Scale (SWLS) for measurement of Subjective well-being, Resilience Evaluation Scale (RES) for resiliency, The Centrality of Religiosity Scale (CRS) for religiosity, The Multidimensional Scale of Perceived Social Support (MSPSS) for social support, and the General Self-efficacy scale (GSES) for self-efficacy. A convenience sample of 1640 Muslim undergraduate students made up the responses. This study's findings suggest that self-efficacy, social support, and religiosity all directly influence resilience. Subjective well-being is directly affected by religion, social support, self-efficacy, and resilience. The association between self-efficacy, social support, self-religion, and subjective well-being is mediated by resilience. Resilience partially mediates the relationship between religiosity, social support, and self-efficacy with subjective well-being. This research has practical implications for the practice of Islamic guidance and counseling, notably the use of religion as a tool to build resilience, for instance, through a more positive reading of difficulties as God's gift for personal growth.